Compression behaviour and shear strength characteristics of a natural silty clay sedimented in the laboratory - Bowden, R; Bowden, Robert Kirk (1988)
﻿ The compression behaviour, shear strength characteristics, and material properties of dense slurries and soft settled beds of natural fine-grained sediments were studied experimentally. Slurries of varying initial density, initial height, and pore fluid salinity were settled one-dimensionally, by self-weight, in the laboratory. Settling behaviour was studied in terms of slurry appearance, particle segregation, height of surface versus time, sediment surface and element settlement rates, and the redistribution of sediment with respect to height and time. Consolidation behaviour was studied in terms of sediment compressibility and pore fluid flow. Shear strength was examined 'in situ' and related to the parameters effective stress and specific volume. Instruments and techniques were developed to facilitate the measurement of low effective stresses, low strengths, and high specific volumes. A small- scale sediment sampler was developed and used in an attempt to study the arrangement of particles within soft sensitive beds. The experimental results revealed numerous fundamental reasons why theoretical models of settling and consolidation are unsatisfactory when applied to dense flocculated slurries and beds of high specific volume, respectively. For the sediment studied, well-defined compressibility and shear strength relationships were observed. Pore fluid flow relationships were non-unique at high specific volumes. The compression behaviour of slurries was found to have a rational basis in terms of electrochemical forces and degrees of particle association. The experimental results are relevant to engineering practice. Recommendations are made regarding future research.